The Case for Natural Gas Fueled Solid Oxide Fuel Cell Power Systems for Distributed Generation. Issue 1 (16th December 2014) - Chick, L.; Weimar, M.; Whyatt, G.; Powell, M.
Abstract Natural‐gas‐fueled solid oxide fuel cell (NGSOFC) power systems yield electrical conversion efficiencies exceeding 55% and may become a viable alternative for distributed generation (DG) if stack life and manufacturing economies of scale can be realized. Currently, stacks last approximately 2 years and few systems are produced each year because of the relatively high cost of electricity from the systems. PNNL has performed cost modeling for production of 270 kW (DC) NGSOFC power systems, sized for light industry or large box stores. If mass manufacturing (10.000 units per year) and a stack life of 15 years can be reached, the cost of electricity from an NGSOFC system is estimated to be about 8, 2 ¢/kWh, well within the range of commercial and residential retail prices at the national level (9, 9–10 ¢/kWh and 11–12 ¢/kWh, respectively). With 5 ¢/kWh in estimated additional benefits from DG, NGSOFC could be well positioned to replace the forecasted 59–77 gigawatts of capacity loss resulting from coal plant closures due to stricter emissions regulations and low natural gas prices.